2012
DOI: 10.1038/nphys2389
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of continuum mechanics for nanometre-wavelength rippling of graphene

Abstract: Understanding how the mechanical behavior of materials deviates at the nanoscale from the macroscopically established concepts is a key challenge of particular importance for graphene, given the complex interplay between its nanoscale morphology and electronic properties 1,2,3,4,5 . In this work, the (sub-) nanometer wavelength periodic rippling of suspended graphene nanomembranes has been realized by thermal strain-engineering and investigated using Scanning Tunneling Microscopy. This allows us to explore the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
208
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(218 citation statements)
references
References 30 publications
10
208
0
Order By: Relevance
“…As a result, the electronic structure in the vicinity of these disorders differs from that in a perfect lattice. More specifically, intrinsic ripples are expected to influence the electrical properties of graphene by changing band gap [239], creating polarized carrier puddles [240] and inducing pseudo-magnetic fields [241]. Whereas wrinkles and crumples result in several electronic phenomena, such as electron-hole puddles [189,242], carrier scattering [195,243], band gap opening [244], suppression of weak localization [245] and quantum corrections [246].…”
Section: Disorders In Graphene Structurementioning
confidence: 99%
“…As a result, the electronic structure in the vicinity of these disorders differs from that in a perfect lattice. More specifically, intrinsic ripples are expected to influence the electrical properties of graphene by changing band gap [239], creating polarized carrier puddles [240] and inducing pseudo-magnetic fields [241]. Whereas wrinkles and crumples result in several electronic phenomena, such as electron-hole puddles [189,242], carrier scattering [195,243], band gap opening [244], suppression of weak localization [245] and quantum corrections [246].…”
Section: Disorders In Graphene Structurementioning
confidence: 99%
“…S1), and then graphene monolayer was grown on it by the low pressure CVD method. During the high-temperature annealing process, the surface Cu atomic vacancies and adatoms emerge through migration and massive diffusion of the surface Cu atoms [21][22][23][24] , as schematically shown in Fig. 1a.…”
mentioning
confidence: 99%
“…Previous studies demonstrated that reconstructions of metals, such as Cu, Ag and Au, could induce both islands and vacancy-islands on the surface [20][21][22][23][24] . In this work, monolayer-vacancy-islands on Cu surface were generated during the synthesis of the graphene.…”
mentioning
confidence: 99%
“…all play a role in the mechanical behavior of graphene. The presence of wrinkles or ripples [19] introduces an additional complexity that may affect the picture [55]. In particular, thermal fluctuations in suspended graphene, in addition to requiring a statistical approach, may amplify non-linear effects [56].…”
Section: Discussionmentioning
confidence: 99%